Learning approaches and academic experiences in university pedagogy students - Huaire-Inacio, Edson Jorge; Dolorier Zapata, Rosa Guillermina; Alfaro Saavedra, Maura Natalia; Riveros Paredes, Pamela Norma (Revista de Ciencias Sociales, 2024)
Learning approaches and academic experiences are constructs of utmost relevance in the student's educational process. With the purpose of building a solid theoretical corpus, this study is carried out, the objective of which is to analyze the association that exists between these variables to understand the difficulties in learning in the university environment. The design was a basic associative type, collecting data from 472 university students of both sexes, using two instruments: the revised study processes questionnaire (R-CPE-2F), and the academic experiences questionnaire (QVA-R). The results show that these variables have a direct relationship (r=0.486) with a significance level of 0.000. It has also been shown that the deep approach has a greater relationship with attitudes towards study and the professional project, while the superficial approach has a greater relationship with personal well-being and interpersonal relationships. It is concluded that the experiences experienced by students as part of their process of adaptation to academic life are complex, but at the same time, they are important predictors in the adoption of preferences, ways and personal perspectives to learn, constituting an important finding. to promote deep learning approaches and improve the academic quality of future professionals.